Giraffes can't dance - Andreae, Giles, 1966-; Parker-Rees, Guy - illus (London : Orchard Books, 1999)
The clumsy giraffe, Gerald, discovers all he needs to become a good dancer is the right music.
K-3
AD570L
M
3.8
Keywords: Giraffe -- Fiction; Animals -- Fiction; Dance -- Fiction; Individuality -- Juvenile fiction; Giraffe -- Juvenile fiction; Stories in rhyme